Preparation of solid dispersion of rutin by spay drying - Van Khanh, Nguyen; Thi Thu, Ta; Anh Tuan, Hoang (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 35 No 2, 2019)
Abstract: The poor solubility of rutin leads to poor bioavailability. The present study is aimed to increase the solubility and bioavailability of rutin using solid dispersion technique. The solid dispersions of rutin were prepared by spray-dried method using β-CD, HPMC E6, HPMC E15, PVP K30, SLS, poloxamer 188 and Tween 80 as carriers. The interaction of rutin with the carriers was evaluated by using methods such as dissolved measurement, Fourier-transformation infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and X-ray diffraction (XRD). The optimization of formulation was carried out by using Central Composite Face design. Independent variables include PVP K30/rutin ratio, Tween 80/rutin ratio, inlet air temperature, and feed flow rate. Dependent variables are the dissolution and product yield. The optimized preparation conditions for rutin solid dispersions were obtained as PVP K30: rutin at a ratio of 5.77, Tween 80: rutin at a ratio of 0.14, inlet temperature of 110.05, flow rate of 1370.9 ml per hour. The results of this study indicate that the solid dispersion of rutin increases significantly the dissolution of rutin in comparison with rutin. The results of the DSC and XRD studies prove the state transition of rutin from crystalline to amorphous. Keywords Rutin, solid dispersion, spray drying, PVP K30, dissolution. References [1] Beatriz Gullón, Thelmo A. Lú-Chau, María Teresa Moreira, Juan M. Lema, Gemman Eibes, Rutin: A review on extraction, identification and purification methods, biological activities and approaches to enhance its bioavailability, Trends in Food Science & Technology 67 (2017) 220-235. https://doi.org/10.1016/j.tifs.2017.07.008. [2] Carla Aparecida Pedriali, Adjaci Uchoa Fernandes, Leandra de Cássia Bernusso, Bronislaw Polakiewicz, The synthesis of a water-soluble derivative of rutin as an antiradical agent, Química Nova 31(8) (2008) 2147-2151. http://dx.doi.org/10.1590/S0100-40422008000800039. [3] Chiou, Win Loung, Riegelman, Sidney, Pharmaceutical applications of solid dispersion systems, Journal of pharmaceutical sciences 60(9) (1971) 1281-1302. https://doi.org/10.1002/jps.2600600902. [4] Xingwang Zhang, Huijie Xing,Yue Zhao, Zhiguo Ma, Pharmaceutical Dispersion Techniques for Dissolution and Bioavailability Enhancement of Poorly Water-Soluble Drugs, Pharmaceutics 10(3) (2018) 1-33. https://doi.org/10.3390/pharmaceutics10030074. [5] Ladan Akbarpour Nikghalb, Gurinder Singh, Gaurav Singh, Kimia Fazaeli Kahkeshan, Solid Dispersion: Methods and Polymers to increase the solubility of poorly soluble drugs, Journal of Applied Pharmaceutical Science 2(10) (2012) 170-175. https://doi.org/10.7324/JAPS.2012.2103. [6] Amrit Paudel, Zelalem Ayenew Worku, Joke Meeus, Sandra Guns, Guy Van den Mooter, Manufacturing of solid dispersions of poorly water soluble drugs by spray drying: formulation and process considerations, International Journal of Pharmaceutics 453(1) (2013) 253-284. https://doi.org/10.1016/j.ijpharm.2012.07.015. [7] P.B. Dalvi, A.B. Gerange, R. IngaleP, Solid dispersion: strategy to enhance solubility, Journal of Drug Delivery & Therapeutics 5(2) (2015) 20-28. https://doi.org/10.22270/jddt.v5i2.1060. [8] Chau Le Ngoc Vo, Chulhun Park, Beom Jin Lee, Current trends and future perspectives of solid dispersions containing poorly water-soluble drugs. European Journal of Pharmaceutics and Biopharmaceutics 85(3) (2013) 799-813. https://doi.org/10.1016/j.ejpb.2013.09.007. [9] I.V. Koval’skii, I.I. Krasnyuk, I.I. Krasnyuk, O.I. Nikulina, A.V. Belyatskaya, Yu. Ya. Kharitonov, N.B. Fel’dman, S.V. Lutsenko, V.V. Grikh, Studies of the Solubility of Rutin from Solid Dispersions, Pharmaceutical Chemistry Journal 47(11) (2014) 612-615. https://doi.org/10.1007/s11094-014-1020-z.